Economic relations between Latin America and Asia-Pacific: recent trends and future challenges - Mattos, Jose Carlos S. (ECLAC Port of SpainTT, 1993)
Looks at the evolution of trade between Latin America and Asia-Pacific during the 1980s. Analyses the main traits of Asia-Pacific foreign direct investment and their possible implications for Latin America. Examines the institutional framework of cooperation in Asia-Pacific and explores the possible future of the economic relations between Latin America and Asia-Pacific.